Nurses' Opinions of Patient Involvement in Relation to Patient-centered Care During Bedside Handovers - Lee Khuan, RN, Ph.D; Muhamad Hanafiah Juni, MBBS, MSc (Elsevier, 2017)
Summary: Purpose: Advocates for societal change and consumerism have been instrumental in popularizing patient involvement in various aspects of health care. Patient involvement in bedside handovers during shift changes should facilitate patient-centered care. This study's purpose was to explore Malaysian nurses' opinions about patient involvement during bedside handovers, and whether patient involvement during bedside handovers reflected patient-centered care. Methods: A qualitative study with four focus-group discussions was conducted with 20 registered nurses from general wards in a Malaysian public hospital. Semi-structured interviews were used to elicit participants' opinions. NVivo 10 software was used for data management and content analysis was used to analyze the data. Results: Several participants used inconsistent methods to involve patients in bedside handovers and others did not involve the patients at all. The participants' interpretations of the concept of patient-centered care were ambiguous; they claimed that patient involvement during bedside handovers was impractical and, therefore, not reflective of patient-centered care. Some nurses' subjective views of patient involvement as impractical during bedside handovers were manifested in their deliberate exclusion of patients from the handover process. Conclusions: Changes in patient involvement and nursing practices congruent with patient-centered care require that nurse educators in hospital settings reform nursing education to focus on fostering of communication skills needed to function in nurse-patient partnerships. Guidelines for patient involvement consistent with patient-centered values should be developed using ward nurses' subjective views and introduced to all registered nurses in practice. Keywords: focus groups, patient-centered care, patient handover, patient involvement